The thermal electrolytic production of Mg from MgO: A discussion of the electrochemical reaction kinetics and requisite mass transport processes. (12th July 2016) - Leonard, N.; Korenko, M.; Larson, C.; Blood, K.; Venstrom, L.J.; Nudehi, S.; Duncan, S.; Diver, R.; Simko, F.; Priscak, J.; Schoer, J.; Kissinger, P.T.; et al.
Abstract: We examined the kinetic and transport processes involved in Mg production from MgO via electrolysis at ca 1250 K with in a eutectic mixture of MgF2 –CaF2, using a Mo cathode, and carbon anode. Exchange current densities, transfer coefficients, and diffusion coefficients of the electroactive species were established using a combination of cyclic and linear sweep voltammetry, chronoamperometry and electrochemical impedance spectroscopy. The cathode kinetics are described by a concentration dependent Butler–Volmer equation. The exchange current density and cathodic transfer coefficient are 11±4 A cm −2 and 0.5±0.12 respectively. The kinetics of the anode are described by two Tafel equations: at an overvoltage below 0.4 V, the exchange current density is 0.81±0.2 mA cm −2 with an anodic transfer coefficient of 0.5±0.1; above 0.4 V overvoltage the values are 0.14±0.05 mA cm −2 and 0.7±0.2 respectively. The diffusion coefficients of the electroactive species are D (Mg 2+ )=5.2±0.6E−5 cm 2  s −1 and D ( Mg 2 OF 4 2 - )=7.2±0.2E−6 cm 2  s −1 . The ionic conductivity of the electrolyte is ca 2.6 S cm −1 . A 3D finite element model of a simple cell geometry incorporating these kinetic and transport parameters suggest that up to 27% of the energy required to drive the electrolysis reaction can be supplied thermally for a current density of 0.5 A cm −2, enabling a reduction in operating cost if the thermal energy is substituted for valuable electric work. Highlights: We have quantified the reaction kinetics for our cathode and anode electrodes. We have quantified the fraction of thermal input to the cell. For a cell running at 0.55 A cm −2, the cell overvoltage is 0.84 V.